Assessment of aerosol effective radiative forcing and surface air temperature response over eastern China in CMIP5 models - Rui-Jin LIU; Hong LIAO (Atmospheric and Oceanic Science Letters, 2017)
The effective radiative forcing (ERF) and associated surface air temperature change over eastern China are estimated using multi-model results from CMIP5 (Coupled Model Intercomparison Project Phase 5). The model results show that, relative to 1850, the multi-model and annual mean aerosol ERF for the year 2005 is −4.14 W m−2 at the top of the atmosphere over eastern China (20°–45°N, 105°–122.5°E). As a result of this ERF, the multi-model and annual mean surface air temperature change in eastern China during 1850–2005 is −1.05 °C, leading to a climate sensitivity of 0.24 °C/(W m−2) in this region.